1990
DOI: 10.3109/00952999009001590
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Treatment of Panic Disorder in Alcoholics: Three Cases

Abstract: It has been postulated that many alcoholics use alcohol to "self-mediate" symptoms of anxiety or panic. Early diagnosis and treatment in this population are both complicated by symptoms of alcohol withdrawal and controversial because of the belief that alcoholics will abuse anxiolytics. The authors present three patients with alcoholism in whom diagnosis of panic was facilitated by intravenous lactate infusion, and whose symptoms were alleviated by clonazepam. All three patients were able to maintain sobriety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Quitkin and co-workers [23] found limited improvement in five patients' anxiety symptoms and alcohN use with imipramine treatment. Baron et al [32] found three alcoholics with panic disorders whose symptoms were alleviated with clonazepam. Brady el al.…”
Section: Mechanisms Of Alcohol Abuse and Dependence And Anxiety Disormentioning
confidence: 99%
“…Quitkin and co-workers [23] found limited improvement in five patients' anxiety symptoms and alcohN use with imipramine treatment. Baron et al [32] found three alcoholics with panic disorders whose symptoms were alleviated with clonazepam. Brady el al.…”
Section: Mechanisms Of Alcohol Abuse and Dependence And Anxiety Disormentioning
confidence: 99%
“…However, better tests may become available. In addition, a nascent literature suggests that physiologic challenge with sodium lactate infusion (Baron et al 1990;Cowley et al 1989;George et al 1989) may have promise for identifying panic disorder in alcoholics.…”
Section: Future Directionsmentioning
confidence: 99%